Aerodynamics of aero-engine installation - Stankowski, Tomasz P.; MacManus, David G.; Sheaf, Christopher T.; Christie, Robert (Sage Publications, 2016)
This paper describes current progress in the development of methods to assess aero-engine airframe installation effects. The aerodynamic characteristics of isolated intakes, a typical transonic transport aircraft as well as a combination of a through-flow nacelle and aircraft configuration have been evaluated. The validation task for an isolated engine nacelle is carried out with concern for the accuracy in the assessment of intake performance descriptors such as mass flow capture ratio and drag rise Mach number. The necessary mesh and modelling requirements to simulate the nacelle aerodynamics are determined. Furthermore, the validation of the numerical model for the aircraft is performed as an extension of work that has been carried out under previous drag prediction research programmes. The validation of the aircraft model has been extended to include the geometry with through flow nacelles. Finally, the assessment of the mutual impact of the through flow nacelle and aircraft aerodynamics was performed. The drag and lift coefficient breakdown has been presented in order to identify the component sources of the drag associated with the engine installation. The paper concludes with an assessment of installation drag for through-flow nacelles and the determination of aerodynamic interference between the nacelle and the aircraft.
Keywords: Engine-airframe integration; through-flow nacelle; aerodynamic interference; computational fluid dynamics; NASA Common Research Model